Craniofacial Morphology of Class II Division 1 Nepalese Population - Bajracharya, Manish; Parajuli, Umesh; Mishra, Praveen; Bhattarai, Prakash; Shrestha, Reetu (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Class II Div 1 is a deviation from normal occlusion and may arise from combination of di" erentcraniofacial components.The objective of this study was to findnd out the different possible dental and skeletalcomponents that lead to Class II Div 1 malocclusion in Nepalese population. Methods: The lateral cephalogramradiographs consisted of 30 males and 30 females between the age group of 18 to 32 years. All the radiographswere traced with hand on acetate paper sheets. All the landmarks were identified, located and marked. Steiner’s analyses and McNamara analysis were done for the cephalometric measurements. The mean valueswere obtained and were compared with the established available values of the Nepalese and Caucasian normsusing independent t-test. Results: Size of the mandible was found to be lesser than the established normalvalues. Prognathic maxilla with retrognathic upper incisors and retrognathic mandible with proclined lowerincisors and was found to be the most common combinations of Class II Div 1 component. Conclusion: Size of the mandible is less than the normal value which is the main cause of the Class II Div 1 pattern in Nepalese population. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/10-13 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7901